Multidimensional Lifestyle Determinants of Hypertension in Indonesia: A Systematic Review with Implications for Population Level Prevention - Henny Kaseger; Gita Sandy Patonengan; Juritno Harmi Gaib; Siska Sibua; Widya Astuti; Helkim Sarino Laode Manika; Suci Rahayu Ningsih (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Hypertension prevalence in Indonesia continues to increase, and unhealthy lifestyle factors such as high-salt diets, physical inactivity, and smoking are widely recognized as important modifiable risk factors. This study aims to examine the association between unhealthy lifestyle behaviors and hypertension in Indonesia. Methods: A systematic review was carried out based on the PRISMA framework, aiming to identify, screen, and evaluate relevant studies published from 2015 to 2025. Articles were searched through the Scopus, PubMed, and ScienceDirect databases, focusing on studies examining the relationship between unhealthy lifestyles and hypertension in Indonesia Results: Of the 19 studies analysed, most employed cross-sectional designs. High salt intake, smoking habits, and low physical activity were consistently associated with higher odds of hypertension. Several studies also indicated stronger associations among individuals with sedentary lifestyles. However, given the predominance of cross-sectional evidence, the findings primarily reflect associations rather than causal relationships. Conclusion: Unhealthy lifestyle factors including high salt intake, low physical activity, smoking, alcohol consumption, stress, and poor sleep patterns are consistently associated with hypertension in Indonesia. These findings underscore the importance of population-level strategies promoting healthy dietary practices, increased physical activity, and behavioral risk reduction. However, given the predominance of cross-sectional evidence, further longitudinal and methodologically robust studies are needed to strengthen causal inference.